2014
DOI: 10.1007/978-3-319-08894-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Receptor Stimulation Decreases Ischemic Brain Damage by Energizing Astrocyte Mitochondria

Abstract: As a leading cause of death in the world, cerebral ischemic stroke has limited treatment options. The lack of glucose and oxygen after stroke is particularly harmful in the brain because neuronal metabolism accounts for significantly more energy consumption per gram of body weight compared to other organs. Our laboratory has identified mitochondrial metabolism of astrocytes to be a key target for pharmacologic intervention, not only because astrocytes play a central role in regulating brain metabolism, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 189 publications
0
7
0
Order By: Relevance
“…A lowered release of glucose from the liver would cause even less glucose to reach the vulnerable portions of the stroke lesions À a region termed the ''penumbra'' which can expand as a lesion grows. 32 Another relevant observation first reported by Bing et al is that liver damage occurs in a middle cerebral artery occlusion rat model. 33 Consequently, etomoxir treatments might be expected to exacerbate any complications with liver function, and further increase the morbidity associated with stroke.…”
Section: Discussionmentioning
confidence: 88%
“…A lowered release of glucose from the liver would cause even less glucose to reach the vulnerable portions of the stroke lesions À a region termed the ''penumbra'' which can expand as a lesion grows. 32 Another relevant observation first reported by Bing et al is that liver damage occurs in a middle cerebral artery occlusion rat model. 33 Consequently, etomoxir treatments might be expected to exacerbate any complications with liver function, and further increase the morbidity associated with stroke.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Cit supplementation was also demonstrated to be neuroprotective through modulating nitric oxide generation (26). Coincidently, these two mechanisms were all involved in rescuing mitochondrial functions, indicating that mitochondrial damage might be a very early event in ischemic stroke and an early sensitive response to hypoxia (27). The increased Ala and Cit in CI were thought to be the protective response of the body in acute phase.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, retinal ischemia caused marked activation of microglia and astrocytes in terms of their protein intensities, morphological changes, increased number and migration throughout retinal cell layers, whereas activation of these glial cells were significantly inhibited by the systemic treatment with P 6 Q peptide. The roles of microglia and astrocytes are complex due to their detrimental and beneficial actions in ischemia (Barreto et al, 2011;Gomes-Leal, 2012;Taylor and Sansing, 2013;Sayre et al, 2014;Hirayama et al, 2015). We previously demonstrated that ProTα protects the brain and retina from ischemic damage, through up-regulation of brain-derived neurotrophic factor (BDNF) or erythropoietin (EPO) (Fujita and Ueda, 2007;Fujita et al, 2009;Ueda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%